Cabergoline-induced cerebrospinal fluid fistulae in macroprolactinomas - Hermann, Elvis Josef; Hertz, Sabine; Nakamura, Makoto; Terkamp, Christoph; Kinfe, Thomas M.; Stolle, Stefan; Leitolf, Holger; Fahlbusch, Rudolf; Krauss, Joachim K. (Langenbeck's archives of surgery, 2025)
Cerebrospinal fluid (CSF) rhinorrhea is a rare complication after dopamine agonist treatment of macroprolactinomas. Up to 90% need surgical repair, however, there are controversial opinions on the necessity of tumor resection upon this occasion. Here we present our long-term follow-up experience in patients who underwent surgical repair of the CSF leak or observation.